Powstanie i rozwój kultury niezależnej w GorzowieWielkopolskim (1980-1989) = The emergence and development of independent culture in Gorzów Wielkopolski (1980-1989) - Kotlarek, Dawid - red.; Buck, Andrzej - red.; Bartkowiak, Przemysław - red. (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The text describes the development of independent culture in Gorzów Wielkopolski in the 1980s, closely connected with the democratic opposition and the Solidarity movement. Underground press played an important role, particularly the journal ?Feniks,? produced clandestinely with the support of opposition activists and voluntary contributions. Independent youth organizations, such as the Independent Youth Movement, were also active and organized educational initiatives, libraries, and self-education circles. They published their own periodicals, including the biweekly ?Szaniec.?By the late 1980s, independent culture had become an important part of the city?s social life. Underground publications and books from abroad circulated widely among residents. The Catholic Church, especially the Gorzów cathedral, served as a key center for opposition meetings and demonstrations. Radio Free Europe and publications from émigré intellectual circles were also important sources of uncensored information. Independent culture contributed to the growth of social awareness and played a significant role in the political transformations that led to the end of the communist system in Poland.
Keywords: Gorzów Wielkopolski; Radio Wolna Europa; NSZZ Solidarność; Ruch Młodzieży Niezależnej; Federacja Młodzieży Walczącej; Instytut Literacki Jerzego Giedroycia; kultura niezależna; prasa podziemna; drugi obieg; Kościół katolicki; opozycja; protest społeczny; komunizm; przemiany społeczne; PRL; Radio Free Europe; solidarity; independent culture; underground press; anti-communist opposition; social changes; Polish People's Republic